Reduction of the RNA Binding Protein TIA1 Exacerbates Neuroinflammation in Tauopathy - LeBlang, Chelsey Jenna; Medalla, Maria; Nicoletti, Nicholas William; Hays, Emma Catherine; Zhao, James; Shattuck, Jenifer; Cruz, Anna Lourdes; Wolozin, Benjamin; Luebke, Jennifer Irene (Frontiers in Neuroscience, 2020)
Neuroinflammatory processes play an integral role in the exacerbation and progression of pathology in tauopathies, a class of neurodegenerative disease characterized by aggregation of hyperphosphorylated tau protein. The RNA binding protein (RBP) T-cell Intracellular Antigen 1 (TIA1) is an important regulator of the innate immune response in the periphery, dampening cytotoxic inflammation and apoptosis during cellular stress, however its role in neuroinflammation is unknown. We have recently shown that TIA1 regulates tau pathophysiology and toxicity in part through the binding of phospho-tau oligomers into pathological stress granules, and that haploinsufficiency of TIA1 in the P301S mouse model of tauopathy results in reduced accumulation of toxic tau oligomers, pathologic stress granules, and the development of downstream pathological features of tauopathy. The putative role of TIA1 as a regulator of the peripheral immune response led us to investigate the effects of TIA1 on neuroinflammation in the context of tauopathy, a chronic stressor in the neural environment. Here, we evaluated indicators of neuroinflammation including; reactive microgliosis and phagocytosis, pro-inflammatory cytokine release, and oxidative stress in hippocampal neurons and glia of wildtype and P301S transgenic mice expressing TIA1+/+, TIA1+/-, and TIA1-/- in both early (5 month) and advanced (9 month) disease states through biochemical, ultrastructural, and histological analyses. Our data show that both TIA1 haploinsufficiency and TIA1 knockout exacerbate neuroinflammatory processes in advanced stages of tauopathy, suggesting that TIA1 dampens the immune response in the central nervous system during chronic stress.